Modelling the Laser Surface Hardening Process in a Steel with a Spheroidized Initial Microstructure - Castro-Cerda, F (Elsevier Ltd, 2024)
A model for predicting hardness and case depth of the hardened layer is proposed, in which it is assumed that the austenite homogenization is concomitant with the dissolution of cementite. The impact of the initial microstructure on the case depth after laser surface heat-treatments is evaluated on three spheroidized hypoeutectoid steels of different carbon contents. Comparison with the experimental hardness measurements show excellent agreement. The model is also able to predict the kinetics of phase evolution during the rapid thermal cycles, allowing an accurate correlation with the microstructure. The results are also compared with an existing model. It is shown that the results of the present model are thermodynamically consistent, revealing discrepancies in the predictions of the latter. © 2024